2014
DOI: 10.1118/1.4873686
|View full text |Cite
|
Sign up to set email alerts
|

Absolute calibration of the Gamma Knife® Perfexion™ and delivered dose verification using EPR/alanine dosimetry

Abstract: This paper shows there is a good agreement between the new calibration method and the currently used one. There is also a good agreement between the calculated and delivered doses especially for Gammaplan v10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The agreement between the ionization chamber and TLDs was within 1% and confirms the accuracy of dose delivery and calculation. This aligns with the findings of McDonald et al (2011), Hornbeck et al (2014 and Zeverino et al (2017), who demonstrated <1% agreement with independent verifications. Although 15 and 25 mm are small fields, they are well within the established size range for performing accurate measurements with suitable small field designated ion chambers as listed in IAEA TRS 483 (Stasi et al 2004, Palmans et al 2018.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The agreement between the ionization chamber and TLDs was within 1% and confirms the accuracy of dose delivery and calculation. This aligns with the findings of McDonald et al (2011), Hornbeck et al (2014 and Zeverino et al (2017), who demonstrated <1% agreement with independent verifications. Although 15 and 25 mm are small fields, they are well within the established size range for performing accurate measurements with suitable small field designated ion chambers as listed in IAEA TRS 483 (Stasi et al 2004, Palmans et al 2018.…”
Section: Discussionsupporting
confidence: 90%
“…Other papers have described the device and initial planning abilities but not a comprehensive description of the commissioning process (Mutaf et al 2013. We have followed a process similar to that previously reported for devices such as the Gamma Knife Perfexion (Ma et al 2009, Hornbeck et al 2014 and Icon (Zeverino et al 2017); however, this treatment delivery system has characteristics that are different from the Gamma Knife and required detailed analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have been conducted to test the precision of EPR/alanine dosimetry for use in the therapeutic dose ranges [3]. The advanced radiotherapy beam modalities and applications that have been verified using alanine dosimetry include intensity modulated radiotherapy (IMRT); electron, proton, carbon ion, and neutron beams radiotherapy; tomotherapy [4]; gamma knife [5]; cyberknife [6]; brachytherapy [7]; small field dosimetry [8]; in vivo dosimetry [9]; electron arc therapy treatment planning verification [10]; total body irradiation [11]; and blood irradiation [12]. In addition, the EPR/alanine dosimetry was used in national audits of radiotherapy centers in other countries, such as the UK [13] and Italy [14].…”
Section: Introductionmentioning
confidence: 99%
“…The absorbed dose rate measured inside a plastic phantom is passed to the LGP and used as the absorbed dose rate in water without any correction. The errors from this substitution have been analyzed, and some alternatives were suggested …”
Section: Introductionmentioning
confidence: 99%
“…The errors from this substitution have been analyzed, and some alternatives were suggested. [10][11][12][13][14] Error occurs because the TMR10 algorithm disregards the inhomogeneity of the materials inside a patient's head. To correct this error, a convolution algorithm that employs the electron-density information of computed tomography (CT) images was added to the LGP.…”
Section: Introductionmentioning
confidence: 99%